Galactose Ingested with a High-Fat Beverage Increases Postprandial Lipemia Compared with Glucose but Not Fructose Ingestion in Healthy Men. Issue 7 (16th April 2020) - Watkins, Jonathan; Simpson, Aaron; Betts, James A; Thompson, Dylan; Holliday, Adrian; Deighton, Kevin; Gonzalez, Javier T
ABSTRACT: Background: Fructose ingestion with a high-fat beverage increases postprandial lipemia when compared with glucose. It is unknown whether other sugars, such as galactose, also increase postprandial lipemia. Objectives: The objective was to assess whether galactose ingestion within a high-fat beverage increases postprandial lipemia relative to glucose or fructose. Methods: Two experiments were conducted, which contrasted different test drinks under otherwise standardized conditions. In Experiment 1, 10 nonobese men (age: 22 ± 1 y; BMI, 23.5 ± 2.2 kg/ 2 ) ingested either galactose or glucose (0.75 g supplemented carbohydrate per⋅kilogram body mass) within a high-fat test drink (0.94 g fat per kilogram body mass). In Experiment 2, a separate group of 9 nonobese men (age: 26 ± 6 y; BMI: 23.5 ± 2.6 kg/m 2 ) ingested either galactose or fructose (identical doses as those in Experiment 1) within the same high-fat test drink. Capillary blood was sampled before and at frequent intervals after ingestion of the test drinks for a 300-min period to determine plasma triacylglycerol, glucose, lactate, nonesterified fatty acid, and insulin concentrations. Paired t tests and 2-way, repeated-measures ANOVA were used to compare conditions within each experiment. Results: The incremental AUC for triacylglycerol was greater following galactose ingestion compared with glucose (127 ± 59 compared with 80 ± 48 mmol⋅L −1 × 300 min, respectively; P  = 0.04) but not compared with fructose (136 ± 74 compared with 133 ± 63 mmol⋅L −1 ×300 min, respectively; P  = 0.91). Plasma lactate concentrations also increased to a greater extent with galactose compared with glucose ingestion (time–condition interaction: P  < 0.001) but not fructose ingestion (time–condition interaction: P  = 0.17). Conclusions: Galactose ingestion within a high-fat beverage exacerbates postprandial lipemia and plasma lactate concentrations compared with glucose but not fructose in nonobese men. These data suggest that galactose metabolism may be more similar to fructose than to glucose, providing a rationale to reassess the metabolic fate of galactose ingestion in humans. This trial was registered at clinicaltrials.gov as NCT03439878.